If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6a + -5)(3a + 1) = 0 Reorder the terms: (-5 + 6a)(3a + 1) = 0 Reorder the terms: (-5 + 6a)(1 + 3a) = 0 Multiply (-5 + 6a) * (1 + 3a) (-5(1 + 3a) + 6a * (1 + 3a)) = 0 ((1 * -5 + 3a * -5) + 6a * (1 + 3a)) = 0 ((-5 + -15a) + 6a * (1 + 3a)) = 0 (-5 + -15a + (1 * 6a + 3a * 6a)) = 0 (-5 + -15a + (6a + 18a2)) = 0 Combine like terms: -15a + 6a = -9a (-5 + -9a + 18a2) = 0 Solving -5 + -9a + 18a2 = 0 Solving for variable 'a'. Factor a trinomial. (-1 + -3a)(5 + -6a) = 0Subproblem 1
Set the factor '(-1 + -3a)' equal to zero and attempt to solve: Simplifying -1 + -3a = 0 Solving -1 + -3a = 0 Move all terms containing a to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -3a = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -3a = 0 + 1 -3a = 0 + 1 Combine like terms: 0 + 1 = 1 -3a = 1 Divide each side by '-3'. a = -0.3333333333 Simplifying a = -0.3333333333Subproblem 2
Set the factor '(5 + -6a)' equal to zero and attempt to solve: Simplifying 5 + -6a = 0 Solving 5 + -6a = 0 Move all terms containing a to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -6a = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -6a = 0 + -5 -6a = 0 + -5 Combine like terms: 0 + -5 = -5 -6a = -5 Divide each side by '-6'. a = 0.8333333333 Simplifying a = 0.8333333333Solution
a = {-0.3333333333, 0.8333333333}
| 14(4m+11)= | | -5(x-3)+2(a-9)= | | forX^2=324 | | 2x^2+12x+36x=0 | | -5(x-31)=115 | | (2a^2b^4+3ab)+(5ab-2a^2b^4)= | | 10x+11=8x+15 | | 10b-2x=16 | | (-4)x(9)-(5)x(-2)= | | 5[x+3]=2[3x+12] | | 2y=2x-1 | | 2n^2+13n-5=2 | | 3x(x)+x-4=0 | | x^2/X^0.5 | | -6(-3-2-5)= | | 208-w=40 | | 7x-1=x+10 | | 171=69-y | | 2x+2xy-6y=0 | | n^2+7= | | 20x^2+16x-15x=12 | | (6)(x)(y)/(2)(x)(y)= | | 28=-x+279 | | b+3(b-4)= | | 3sin^2(x)+2sin(x)=5 | | 2x+2xy-6=0 | | 3x-3x=-3 | | -3y-7=-10y+21 | | 400=1.5x | | 144x^2-121y^2=0 | | 4x^2=-2x | | -8(-8m-6)=-6m-22 |